PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 8 KOTA PEKANBARU - Putri, Noprita Neni; Alim, Jesi Alexander; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted on May 2015. The data shown the either learning process increased. The total of students who passed 18 and 12 people failed. The daily examination increased is 60% with an average was 66,3. The daily examination increased also is 77% with average was 80,3 the total of students who passed 23 and 7 people failed. Based on the explanation above it can be concluded that the implementation of quantum teaching increased students’ achievement the result of mathematics studies of students III grade of State Elementary School 8 Pekanbaru.Keywords : Quantum Teaching, Students Achievement The Result Of Mathematics Studies